PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SDN 038 SEKELADI HILIR - Lela Kirana; Mahmud Alpusari; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Absract: The problem this research is the students achievement of sains studies SDN 038 Sekeladi Hilir fourth graderes still low with an average value of 63,13 and minimum completeness criteria (KKM) sains studies is 70. Between students, amounting to 24 people only 9 students who achieve classical KKM with 37,5 %. This research is Classroom Action Research (CAR), which aims to improve the student achievement of sains studies class V at SDN 038 Sekeladi Hilir with implementation approach STAD. Formulation of the problem: Is the implementation of approach STAD can improve students achievement of sains studies at SDN 038 Sekeladi Hilir. The research was conducted on April 12, 2016 to Mei 03, 2016 by 2 cycles. Subjects were students of SDN 038 Sekeladi Hilir, totaling 24 people who use the data source. The data collection instruments in this thesis is a teacher and students activities sheets and students achievement. This thesis presents the results obtained each day before the action an improve in base score cycle with the average being 63,13. in the first cycle improve an average 74,67 and an improve in the second with an average of 87,58. Activities of the teacher in the learning process in cycle of 58,33% and the second meeting improve 79,16%. Cycle II first meeting and the second meeting improve 83,33% and the second meeting improve 91,67%. Results of data analysis of students activities in the first cycle with the first meeting of an average 54,17% and a second meeting improve to 70,83% . Cycle II first meeting improve 79,17% and the second meeting improve to 87,5%. Resultsin the class V at SDN 038 Sekeladi Hilir that the implementation of approach STAD can improve student achievement of sains studies at fourth graderes SDN 038 Sekeladi Hilir.Key Words : The implementation of Approach Student Teams Achievement Division (STAD).